2021
DOI: 10.3390/molecules26113453
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activities of Aminophenoxazinones

Abstract: Aminophenoxazinones are degradation products resulting from the metabolism of different plant species, which comprise a family of natural products well known for their pharmacological activities. This review provides an overview of the pharmacological properties and applications proved by these compounds and their structural derivatives during 2000–2021. The bibliography was selected according to our purpose from the references obtained in a SciFinder database search for the Phx-3 structure (the base molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 105 publications
(164 reference statements)
0
8
0
Order By: Relevance
“…Numerous studies have been performed on the isolation and chemical and biological characterization, and these studies are still increasing. These investigations have also confirmed that families such as alkaloids [ 1 ], peptides [ 2 ], phenoxazines [ 3 ], amines [ 4 ], or nitrogenous sesquiterpenoids [ 5 ] could show outstanding activities of pharmacological or agronomic interest. The alkaloid family is one of the most relevant of these, given its production by a wide range of living beings, its structural variety, as well as the biological activities that have been discovered a long time ago.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Numerous studies have been performed on the isolation and chemical and biological characterization, and these studies are still increasing. These investigations have also confirmed that families such as alkaloids [ 1 ], peptides [ 2 ], phenoxazines [ 3 ], amines [ 4 ], or nitrogenous sesquiterpenoids [ 5 ] could show outstanding activities of pharmacological or agronomic interest. The alkaloid family is one of the most relevant of these, given its production by a wide range of living beings, its structural variety, as well as the biological activities that have been discovered a long time ago.…”
Section: Introductionmentioning
confidence: 80%
“…Cinnabarin (157) showed an antitumor activity with an IC 50 value of 13 µM [59]. It should be noted that other phenoxazones, particularly Phx-1 and Phx-3 (159 and 160, Figure 9), are well-studied compounds for the development of anticancer drugs, as reviewed by Zorrilla et al (2021) [3]. In the SAR study [59], pycnoporin (99, Figure 7) showed a moderate antitumor activity, whereas cinnabarinic acid (158, Figure 9) was not active.…”
Section: Structure−activity Relationship Studiesmentioning
confidence: 99%
“…3 H -Phenoxazin-3-one and its derivatives are widely distributed in nature in microorganisms and fungi, and they represent the key structural units of many important drugs with antibacterial, antifungal, anticancer, anti-inflammatory, and antiviral activities [ 1 2 ]. Due to the presence of several reactive centers in the structure, 3 H -phenoxazin-3-ones can easily be accessed through oxidative couplings of o -aminophenols [ 3 4 ] or N -aryl- o -benzoquinone imines [ 5 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aminophenoxazinones are highly colored dyes, possessed a number of promising properties like anticarcinogenic, antifungal, antiparasitic, antibacterial or antimicrobial activities ( Zorrilla et al, 2021 ) which consist of tricyclic structures with double bonds in aromatic systems containing oxygen and nitrogen atom ( Pasceri et al, 2013 ). Thus, aminophenoxazinones are good candidate food grade pigments.…”
Section: Introductionmentioning
confidence: 99%